PEMBIASAAN SHALAT BERJAMA’AH DALAM MEMBENTUK KARAKTER SISWA YANG KOMUNIKATIF DAN BERTANGGUNG JAWAB DI SMA MUHAMMADIYAH 4 PORONG SIDOARJO - Aviyah, Iin Inayatus; Salahuddin, Rahmad (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2024)
Character education starts from childhood. Religious habits that are carried out to form a religious character, such as congregational prayer create a communicative and responsible character, this phenomenon is an attraction for researchers to carry out this research. The research method used is qualitative by emphasizing the socially constructed nature of reality, namely establishing a close relationship between the researcher and those being researched. The locus of this research is SMA Muhammadiyah 4 Porong. The data collection techniques used are interviews, observation, and documentation analysis, while the informants are principals, teachers, and some students. The results of the research show that students at SMA Muhammadiyah 4 Porong who carry out Islamic habits mean providing good things to students, such as congregational prayer, muraja'ah together. It appears to researchers that these characters support their sense of responsibility, good attitudes, and attitudes. and more serious in carrying out their duties in learning. The disciplined character in carrying out group prayers and then murajaah together is an Islamic character which is an illustration of students' responsibility in carrying out their duties and responsibilities as a Muslim who adheres to their religion. The implications of research regarding the habit of praying together in forming the character of communicative and responsible students include: 1) Educational practitioners know the importance of religious education in schools, 2) Implementing curriculum integration in schools, 3) Teachers and school staff have a complex role in fostering students' sense of responsibility in their daily lives, 4) Establishing collaboration between teachers and parents.